"They're describing Yelp in 1992!": revisiting the Blacksburg Electronic Village. Issue 1 (3rd April 2022) - Kneese, Tamara
Abstract: Launched in 1993, the Blacksburg Electronic Village (BEV), located in Blacksburg, Virginia and connected to Virginia Tech, was an experiment in community computing. Through its funding models and technologies, the BEV united government, municipal, corporate, and university interests. While it received media attention and scholarly engagement in its prime, the BEV has not yet been reconsidered as part of the larger critical history of virtual communities and platforms. Through primary and secondary accounts of the BEV, I argue that the BEV's trajectory is emblematic of how communities learn to negotiate going online for the first time, balancing the visions of designers and funders with those of users. The BEV was both a prototype and, later, a laboratory for participatory design, connecting an entire town to the World Wide Web. Its online listings of local businesses and e-commerce hub, known as the Village Mall, applications like MOOSburg—a multi-user domain—and an interactive Virtual School wired the town. The BEV was a small, rural, geographically-situated community used by senior citizens and college students alike, but it was not always inclusive. I point to critical scholarship about the BEV and other early electronic communities to situate the BEV within larger theoretical considerations regarding the relationship between electronic communities and local geographies, the different expectations of designers versus users, and the problems of inclusion, moderation, and control, even when access is provided.